Improved GaN[sub x]As[sub 1−x] quality grown by molecular beam epitaxy with dispersive nitrogen source - Wang, S. Z. (2013)
A modified mode for GaAsN growth using solid-source molecular beam epitaxy in conjunction with dispersive nitrogen to avoid the bombardment effect of energetic nitrogen ions is reported. High-quality GaAsN epilayers and good GaAsN/GaAs interfaces were achieved using this growth mode. The results suggest that the surface of samples grown using dispersive nitrogen has fewer defects than those grown using the direct nitrogen beam. The optical quality of GaAsN samples grown using the dispersive nitrogen technique was found to improve, due to the lower nitrogen ion bombardment effect. This growth technique is expected to be advantageous for growing high-quality GaAsN materials for optoelectronic applications.